Kinetics and Phenotype of the CD4 T Cell Response to Influenza Virus Infections - Hornick, Emma E.; Zacharias, Zeb R.; Legge, Kevin L. (Frontiers in Immunology, 2019)
Influenza A virus (IAV) is a leading cause of respiratory infections, with increased risk of severe illness and death in the very young, aged, and immunocompromised individuals. In both mice and humans, IAV-specific T cell responses are protective during primary as well as homologous and heterologous challenge infections. Many mouse studies have focused on CD4 T cells specific for a single, known model or IAV antigen. However, studies have demonstrated that the IAV-specific CD4 T cell response comprises many epitopes spread across multiple viral proteins. Therefore, herein we track the antigen-experienced CD4 T cell response using the surrogate markers CD49d and CD11a. This novel surrogate marker method allows us to characterize the full IAV-specific CD4 T cell response without the potential bias that could occur when examining an individual Ag-specificity. Our findings demonstrate that the immunodominant I-Ab-binding NP311-325 epitope often used in studies of IAV-specific CD4 T cells represents only about five percent of the total IAV-specific CD4 T cell response. Further we find that the kinetics of the full pulmonary CD4 T cell response is similar to that of NP311-specific T cells and that the full CD4 T cell response in the lungs is predominantly composed of cells expressing the Th1 transcription factor T-bet, with smaller but significant portions of the response expressing the Treg and Tfh associated transcription factors Foxp3 and Bcl-6, respectively. Interestingly, although Th1 cells are the most abundant Th subset in the lungs of both BALB/c and C57Bl/6 mice following IAV, the relative abundance of Treg and Tfh is reversed in the different mouse strains. In BALB/c mice, Foxp3+ cells are more abundant than Bcl6+ cells, whereas in C57Bl/6 mice, there are more Bcl6+ cells. As a whole, these data highlight the diversity of the endogenous CD4 T cell response to a primary IAV infection, providing an important context for past and future studies of the IAV-specific CD4 T cell response.